PENGARUH PROGRAM PENDIDIKAN GURU PENGGERAK MELALUI KOMPETENSI GURU DAN MUTU PELAYANAN PENDIDIKAN TERHADAP KINERJA GURU DI KABUPATEN TEMANGGUNG - Teta Novianti; Fakhruddin; Widiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of the Teacher Leadership Program (PGP) on teacher competence, quality of educational services, and teacher performance in Temanggung Regency. The research employed a quantitative approach with an explanatory design. A total of 171 teachers were randomly selected as samples from 309 PGP graduates. Data were collected through questionnaires and analyzed using Spearman’s correlation test. The findings indicate significant relationships between teacher competence, educational service quality, and teacher performance. However, the PGP variable demonstrated a negative correlation with teacher performance, although this relationship was moderated by teacher competence and educational service quality, which strengthened and shifted the relationship in a positive direction. The results highlight the importance of enhancing competence and service quality to maximize the impact of the PGP on teacher performance.